GRATIFIKASI DALAM PERSPEKTIF HADIS - Mukhlis Mukhtar; Andi Herawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
The prohibition of state administrators or state sivil servants (ASN) from receiving gratuities has occurred since the time of the Prophet saw. until now. The prohibition is one of the values of Islamic teaching brought by the Prophet saw. who until now lives in the midst of people’s lives (living sunah). On the other hand, the Prophet saw. ordered to give gifts to each other, but giving gifts is considered gratification if it is given to state officials or ASN. Because gratification is actually intended to stir the hearts of state officials or ASN so that in the future is can facilitate the goals or desires of the giver. Gratification is considered a bribe, if it is related to his position and does something that is contrary to his obligations or duties.